Rosuvastatin Plus N Acetylcysteine to Prevention of Contrast Induced Acute Kidney Injury in Patients with Low Mehran Risk Score - Habib, Mohammed (Journal of Society Medicine, 2024)
Introduction: Contrast induced acute renal injury is the third leading cause of hospital-acquired acute kidney injury, several protective treatments options have been developed among patients undergoing percutaneous coronary intervention (PCI). Our trial aimed to comparison between high dose rosuvastatin versus rosuvastatin plus N acetylcysteine to prevention of contrast induced acute kidney injury in patients undergoing elective PCI at Alshifa hospital in Gaza. Methods: Randomize control trial included 100 patients who undergoing elective PCI at Alshifa Hospital in Gaza, Group A (50 patients) patients received 40 mg rosuvastatin orally once daily for 3 days, on dose before undergoing PCI and two dose after PCI. Group B (50 patients) patients received 40 mg rosuvastatin orally once daily for 3 days, on dose before PCI and two dose after PCI plus N-acetylcysteine 1200 mg orally twice daily every 12 hours for two days, the first dose before PCI and other 3 doses after PCI. All patients were measuring serum creatinine level, creatinine clearance and blood urea nitrogen (BUN) before PCI and (2-3) days after procedure. Results: In Group A, nonsignificant reduction of serum creatinine level (P: 0.90), creatinine clearance (P: 40) but significant reduction BUN was seen after treatment (P: 0.017). In Group B, Significant reduction of serum creatinine level, and BUN (P< 0.001).  But creatinine clearance not significant changes were seen after treatment (P:0.72). On other hand comparison between two group was significant reduction of serum creatinine level (P: 0.046) in group B, but creatinine clearance and BUN were not significant (0.41, 0.34) respectively. Conclusion: High dose rosuvastatin plus N-acetylcysteine compared rosuvastatin had significant reduction only of creatinine level without reduction in BUN and creatinine clearance among patients undergoing PCI.